Frequency of Intestinal Parasites in Tehran - H Oormazdi; E Razmjou; AR Meamar; J Shamseddin; L Akhlaghi (Iranian Journal of Parasitology, 2009)
"nBackground: For a long time, intestinal parasite infections are among the major problems of public health in Iran. Our aim was epidemiological studies on the frequency of intestinal parasites in patients referred to three hospitals in Tehran during 2007-2008."nMethods: During 2007-2008, by simple random selection, 1000 stool samples were collected from Milad, Hazrat-e-Rasoul and Shahid Fahmideh hospitals in Tehran, Iran. We examined the samples using direct smear, formol-ethyl acetate concentration, Agar-plate culture and Ziehl-Neelsen staining technique."nResults: The frequency of intestinal parasites were: Blastocystis hominis 12.8%, Giardia lamblia 2.5%, Entamoeba coli 4.8%, Iodamoeba butschlli 0.9%, unknown 4 nuclei cysts 0.4%, Endolimax nana 3.2%, Chilomastix mesnili 0.4%, Strongyloides stercoralis 0.1%, Hymenolepis nana 0.2% and Taenia saginata 0.2%. Coccidian parasites were not found. Results show that infection with intestinal parasites does not statistically significant according to sex and age."nConclusion: The intestinal parasites, especially helminthic infections have been decreased during recent years.